Burdened by proof an assessment of Merceditas Navarro-Gutierrez as Philippine Ombudsman - Cristobal, Mely Ann Emerie arroyo (2012)
"This undergraduate thesis assesses Merceditas Navarro-Gutierrez and her management of the Office of the Ombudsman. It uses the data gathered from the documents of the impeachment case against Gutierrez, interviews with the employees of the Office of the Ombudsman and reporters covering the Ombudsman beat. By examining the policies and management during Gutierrez's term, the allegations in the impeachment case and the root of the negative public opinion were explained. This explanatory story pointed to the consolidation of power to the head of the office, a policy put in place by Gutierrez, as the main reason of the inefficiency of the Office of the Ombudsman. This research argues that it was her leadership and management of the agency that led to the lost of public's trust in the Office of the Ombudsman."